PENINGKATAN KINERJA BISNIS UKM BATIK JAMBI MELALUI ENTREPRENEURSHIP TRAINING - ADE OCTAVIA (Jurnal Manajemen Terapan dan Keuangan, 2016)
Abstract The purpose of this research is to analyze the relationship of entrepreneurship training and business performance of small and medium enterprises. The approach used is the survey sample  with respondents SME’s batik jambi. By using multiple regression analysis found that entrepreneurship training consisting of presentations, negotiations, communications, marketing management, financial management  and production have a significant influences on performance of the business. Keywords: entrepreneurship training, marketing, business performance, small and medium enterprises